História e Cultura Afiro-Brasileira e Africana na Educação Infantil: um estudo de caso em uma escola da rede pública de ensino do municipio de Candeias-BA - Batista, Gabriele de Jesus (2025)
This research aims to understand how the implementation of Afro-Brazilian and African History and Culture has taken place in the pedagogical practice of Early Childhood Education at the Gisella Tygel Education Center, located in Candeias, Bahia. To this end, the following specific objectives were defined: to identify the perceptions of the teachers and the school management member regarding the relevance of studying Afro-Brazilian and African History and Culture; to analyze the school’s pedagogical practice concerning the teaching of this theme in the classroom; and to examine whether the school’s Political-Pedagogical Project includes a plan or proposal focused on the teaching of Afro-Brazilian and African History and Culture. The study seeks to answer the following research question: In what ways have the pedagogical practices of Early Childhood Education at the Gisella Tygel Education Center addressed AfroBrazilian and African History and Culture? To answer this question and achieve the proposed objectives, a qualitative approach was adopted (Minayo, 2007), employing an ethnographicinspired method and a case study strategy (André, 2013; Ludke; André, 1986), given their alignment with the research purpose. Data were collected and generated through semistructured interviews with two Early Childhood Education teachers—one from the G4 class and one from the G5 class—and a member of the school management team; participant observation conducted during July, August, and September 2024 in the participating classrooms; field notes; analysis of the institution’s Political-Pedagogical Project; and a profile questionnaire (Ludke; André, 1986; Gil, 2011). Thematic analysis, as proposed by Bardin (1997), was used to examine the data. The results reveal the absence of structured projects and proposals focused on teaching Afro-Brazilian and African History and Culture in the school setting, indicating that actions related to the theme occur only in the month of November. The findings also highlight the lack of initial and continuing education as a key challenge to be overcome in order to ensure that pedagogical practice effectively addresses Afro-Brazilian and African History and Culture in Early Childhood Education.